THE EFFECT OF SCIENCE LEARNING BASED ON AN INTEGRATED SCIENTIFIC APPROACH TO LOCAL POTENTIAL ON THE SCIENCE PROCESS SKILL OF THE STUDENT - Cahyaningtyas, Riza Nur; Wilujeng, Insih; Suryadarma, I Gusti Putu (Department of Integrated Science, Faculty of Mathematics and Natural Sciences, Universitas Negeri Semarang in Collaboration with Perkumpulan Pendidikan IPA Indonesia, 2017)
The present study aimed to analysis the aftermath of science learning based on an integrated scientific approach to local potential, onion agriculture, towards the science process skill of 7th grade of junior high school students. The study was a quasi-experimental research with non-equivalent control group design. The object of this experiment was all classes in the 7th grade of Wedarijaksa 2 junior high school. Cluster random sampling was used to gather the sample, as the result, two over seven classes were randomly chosen. Data that be used in the research were the result of science process skill test. Data were analyzed using One-way Anova. The result shows that there is a significant impact of science learning based on scientific approach to local potential, in this case is onion agriculture, towards process science skill of the students.